Outcomes and costs of home hospitalisation compared to traditional hospitalisation for infectious diseases in Israel: a cohort study - Limor Adler; Ilan Yehoshua; Sharon Baruch Gez; Bar Cohen; Beatriz Hemo; Angela Irony; Khaled Abou Houssien; Omri Shental; Shirley Shapiro Ben David (BMJ Open)
Objectives This study aims to evaluate and compare health outcomes and costs between home hospitalisation and traditional hospitalisation for three common diagnoses—cellulitis, urinary tract infection (UTI) and pneumonia.Design A retrospective cohort study.Setting Primary care, nationwide.Participants 1311 patients in home hospitalisation and 992 in traditional hospitalisation.Interventions The primary intervention is home hospitalisation, compared with traditional hospitalisation. The intervention was performed according to medical considerations by a specialised team, and this study was done retrospectively to evaluate it.Primary and secondary outcome measures Primary measures included healthcare costs, length of hospitalisation, referrals for further medical services and mortality.Results Costs of home hospitalisation were lower compared with traditional hospitalisation (6056 vs 9619 NIS for pneumonia, 6011 vs 9767 NIS for cellulitis, 6466 vs 8552 NIS for UTI and p value<0.05). The length of home hospitalisations was shorter for pneumonia and cellulitis (5.01 vs 6.05 days, p value 0.001 and 5.3 vs 6.1 days, p value<0.001, respectively). Likewise, for pneumonia and cellulitis, home-hospitalised patients had fewer ED referrals 30 days after discharge (13.7% vs 24%, p value<0.001 and 13.5% vs 19.8%, p value 0.002, respectively). No differences were found in recurrent hospitalisation and mortality 7 and 30 days after discharge.Conclusions Primary care physicians should consider home hospitalisation for these diagnoses as an alternative to traditional hospitalisation. Policymakers should encourage Primary care physicians to use home hospitalisation, as it has financial advantages and better health outcomes.